VD_FINDINFO Arrêt / 2017 / 566 vom 31. Mai 2017 - VD Tribunal cantonal (2017)
DROIT DE DÉTERMINER LE LIEU DE RÉSIDENCE, DÉMÉNAGEMENT, CURATELLE ÉDUCATIVE | 310 CC, 442 al. 1 CC, 442 al. 5 CC, 445 al. 3 CC